Polymorphism and solid–solid phase transitions of hydrogen bonded 2-adamantanol and 2-methyl-2-adamantanol compounds. Issue 20 (21st April 2022) - Salvatori, Alejandro; Negrier, Philippe; Massip, Stephane; Muñoz-Duque, Antonio; Lloveras, Pol; Barrio, Maria; Tamarit, Josep-Lluís
Abstract : The polymorphic behavior at normal pressure as a function of temperature of 2-adamantanol (C10 H16 O) and 2-methyl-2-adamantanol (C11 H18 O) has been investigated by single-crystal and powder X-ray diffraction as well as differential scanning calorimetry. Abstract : The polymorphic behavior at normal pressure as a function of temperature of 2-adamantanol (C10 H16 O) and 2-methyl-2-adamantanol (C11 H18 O) has been investigated by single-crystal and powder X-ray diffraction as well as differential scanning calorimetry. Our findings demonstrate that the previously reported specific heat anomaly at around 238 K for C10 H16 O consists of a single-crystal to single-crystal IV–III high-order phase transition without change of space group ( P 1̄, Z = 6, Z ′ = 3). The combined use of single-crystal and powder X-ray diffraction demonstrates that phase IV would be fully ordered only at 0 K. As the temperature increases, the hydrogen atoms linked to the oxygen atoms are found to be disordered between two sites, reaching an occupancy factor of 50% each at the IV–III transition temperature. An order parameter related to the continuous change of the β lattice parameter can account for this IV–III high-order phase transition. Furthermore, a mechanism is proposed for the first-order transition from phase III to phase II (monoclinic, C 2/ m, Z = 12, Z ′ = 1.5), in which O atoms are disordered between 2 sites (50% occupancy factor). Single-crystal X-ray diffraction of the low-temperature phase of C11 H18 O, stable below 368 K, shows unambiguously a fully ordered orthorhombic structure ( Pbcn, Z = 16, Z ′ = 2), contrary to the previously reported space group ( Pcc 2). Below melting temperature, both compounds display a high-temperature orientationally disordered (plastic) phase ( Fm 3̄ m, Z = 4), like most of the adamantane derivatives.